2017
DOI: 10.5539/ies.v10n2p35
|View full text |Cite
|
Sign up to set email alerts
|

Students Evaluation of Faculty

Abstract: This study aimed to investigate how students evaluate their faculty and the effect of gender, expected grade, and college on students' evaluation. The study sample consisted of 5291 students from Tafila Technical University Faculty evaluation scale was used to collect data. The results indicated that student evaluation of faculty was high (mean = 4.14, S.D. = 0.79) and there were statistically significant differences in students' evaluation attributed to students' gender, college and expected grade in the cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…The reviewed study exploited a relatively small number (30) of participants whose findings were difficult to generalize the findings beyond the situation and participants, while the present study used a larger sample size of 283 students which boosted credibility and generalization of the results. The findings from a study conducted by Thawabieh [24] in Tafila Technical University in Israel demonstrated that student's self-assessment accuracy was higher especially when criteria were provided in relation to the teacher's assessment. Data were gathered using two test tools; which were teacher made and two student's selfassessment tool.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reviewed study exploited a relatively small number (30) of participants whose findings were difficult to generalize the findings beyond the situation and participants, while the present study used a larger sample size of 283 students which boosted credibility and generalization of the results. The findings from a study conducted by Thawabieh [24] in Tafila Technical University in Israel demonstrated that student's self-assessment accuracy was higher especially when criteria were provided in relation to the teacher's assessment. Data were gathered using two test tools; which were teacher made and two student's selfassessment tool.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hemşirelik eğitim programlarının değerlendirme sürecinde kullanılabilecek birçok model mevcuttur. Bu modellerden biri de Context (bağlam), Input (girdi), Process (süreç) ve Product (ürün) kelimelerinin kısaltması olan ve eğitim programlarını bu dört alanda değerlendiren CIPP değerlendirme modelidir [8][9][10] . CIPP değerlendirme modeli, hemşirelik eğitim programının genel kalitesinin ve değerinin belirlenmesine rehberlik edebilecek teorik bir çerçeve sağlamaktadır.…”
Section: Introductionunclassified